2018
DOI: 10.1186/s12302-018-0177-6
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Ibuprofen, Cetirizine, and Naproxen by PAN-MWCNT/TiO2–NH2 nanofiber membrane under UV light irradiation

Abstract: BackgroundIn this study, the photodegradation of three pharmaceuticals, namely Ibuprofen (IBP), Naproxen (NPX), and Cetirizine (CIZ) in aqueous media was investigated under UV irradiation. The photocatalyst used in this work consists of surface functionalized titanium dioxide (TiO2–NH2) nanoparticles grafted into Polyacrylonitrile (PAN)/multi-walled carbon nanotube composite nanofibers. Surface modification of the fabricated composite nanofibers was illustrated using XRD, FTIR, and SEM analyses.ResultsSets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…It was indicated that the residual amino acids in test solutions had a contribution on the magnitude of the protective effects for NX photodegradation. Previous studies showed that the photodegradation efficiency of the irradiated compound was dependent on its initial concentration [ 22 ]. In this experiment, it was indicated that amino acids that had protective potencies at a lower concentration might tend to be degradable by photo-irradiation, compared to that at higher concentration.…”
Section: Resultsmentioning
confidence: 99%
“…It was indicated that the residual amino acids in test solutions had a contribution on the magnitude of the protective effects for NX photodegradation. Previous studies showed that the photodegradation efficiency of the irradiated compound was dependent on its initial concentration [ 22 ]. In this experiment, it was indicated that amino acids that had protective potencies at a lower concentration might tend to be degradable by photo-irradiation, compared to that at higher concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the intermediates and final products that are generated in the wake of these photochemical reactions may also change the pH of the environment. Moreover, the drug may be more stable in its ionized or non-ionized form and may undergo specific acid-base catalysis in aqueous solutions [26,27]. It is well-known that the photodegradation of drugs is significantly affected by the pH of the environment because the changes in pH can promote or inhibit photolysis [26].…”
Section: Percentage Of Degradation Of Eme Epi and Ketmentioning
confidence: 99%
“…In addition, the intermediates and final products that are generated in the wake of these photochemical reactions may also change the pH of the environment. Moreover, the drug may be more stable in its ionized or non-ionized form and may undergo specific acid-base catalysis in aqueous solutions [26,27].…”
Section: Percentage Of Degradation Of Eme Epi and Ketmentioning
confidence: 99%
“…In one bench-scale study it was found that the ibuprofen removal rates ranged between 2 and 80% with varying PAC concentrations in the 1-20-mg/L range (Westerhoff et al, 2005). • Ultraviolet (UV) radiation with an intensity designed to simulate solar irradiation was reported to cause a range of 62-67% ibuprofen photodegradation in various source waters spiked with high contaminant concentrations (10-40 mg/L) (Mohamed et al, 2018).…”
Section: Abatement Techniquesmentioning
confidence: 99%